indonesia - Rindi Metalisa; Diva Nurfitria Arda; Dwi Adheka Sella; Yulia Adriana; Farhan Ariqqulhuda; Agung Surya Pradana; Dodi Suprayitno; Imanuela Octasya Saragih; Silvy Amelia Ritonga; Anita Simanjuntak; Lina Pebrianti Manullang (Unri Conference Series: Community Engagement, 2022)
Drug abuse is still prevalent among the public, especially among the younger generation. Efforts have been made to prevent drug abuse among teenagers and students, one of which is by socializing on the dangers of drugs and prevention. Socialization is believed to be the most effective and economical way to prevent drug abuse. Socialization methods include discourse, questioning and discussion. This socialization aims to improve understanding and provide information regarding drug hazards and prevention. There is an increase in student knowledge compared to before socialization. So that students' awareness of the dangers of drugs is better and students are able to guard themselves and be alert to the spread of drugs.